POLITIK HUKUM PEMBENTUKAN MAJELIS KEHORMATAN NOTARIS - Winda Ayu Swastika (Lex Renaissance, 2016)
AbstractPrevious roles and authority of the Supervisory Council of Regions in almost identical to the role of the Notary Honorary Council had been abolished by the Constitutional Court of the Republic of Indonesia in Decision Number 49 / PUU-X / 2012 as contrary to the constitution of the state of Indonesia. Problems in this study, first, what is the legal political formation Honorary Council of Notaries in Law No. 2 of 2014? Second, how the legal protection of the Notary Act No. 2 of 2014? This research is a normative juridical research. Based on research by the authors concluded that with the issuance of permenkumham No. 7 2016 then clearly setting the organizational structure, duties, responsibilities and obligations of Honorary Council of Notaries, and it can be concluded that the legal protection of notaries who used to be done by the Council of Regional Supervisor particularly regarding decision minuta deed (borrowing) and call the police now Notary by the authority of the Honorary Council of Notaries. With the release of permenkumham No. 7 of 2016 is expected to vacuum cornerstone of legal protection for the Notary profession for 2 (two) years can be resolved.Keywords: Politics, Law, Honorary Council, Notary.